Nim extracts on the control of Spodoppher frugiperda in corn - Uchôa, Luiz Romário; Almeida Filho, Ivan Isidorio de; Souza, Joaci Pereira; Santos, Cristian de França; Santos, Daniel Lima (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Corn is a crop of great economic importance, however, it is greatly impaired by the attack of the carcass caterpillar, where chemical control is used, which is toxic to biodiversity, necessitating the development of natural control alternatives. Thus, the objective of this study was to evaluate the effects of different extracts derived from neem in the control of carpiaceous caterpillar (Spodoptera frugiperda) in irrigated corn cultivation. The experiment was conducted under field conditions at the Federal Institute of Education, Science and Technology of Ceará, Campus Iguatu. For the experiment, a randomized complete block design was used, with 6 treatments and 4 replications totaling 24 plots. The neem-based treatments used were: without insecticide; fruits; sheets; leaves + seeds; commercial oil and chemical insecticide. The population level of the caterpillars (S. frugiperda) as well as their length at 18, 36, 54, 72 and 90 days after planting were evaluated. In parallel, a visual evaluation of the damage to the cartridge and expanded leaves of maize plants was carried out, based on a visual scale (Dives scale). The treatment with the neem fruits presented the best results in all analyzed variables, and could be used in substitution of chemical products in the control of the carcass caterpillar. For the number and length of caterpillars, treatments with fruits and chemical insecticide stood out from the others. Regarding the damages, the treatments with fruits, leaves, fruits plus leaves and chemical insecticide did not have statistical difference between them. The treatment with neem commercial oil did not present satisfactory results.